Experimental studies and a double gate JFET model for analog integrated circuits - Y. D. Galkin; O. V. Dvornikov; V. A. Tchekhovski; N. N. Prokopenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
One of directions of improving parameters of analog integrated circuits is a development of new and modernization of existing designs of integrated elements without significantly changing of a technological route of integrated circuit manufacturing with a simultaneous creation of new integrated elements models. The article considers the results of experimental studies of the double gate junction field-effect transistor manufactured according to the 3CBiT technological route of JSC Integral. Based on the obtained results, the electrical model of double gate junction field-effect transistor is proposed, which describes the features of its application in analog integrated circuits. Comparison of I-V characteristics of measurements results and created model simulation are presented. A small capacity and a reverse current of a double gate junction field-effect transistor top gate, an ability to compensate for the DC (direct current) component of an input current provide a significant improvement in the characteristics of analog integrated circuits such as electrometric operational amplifiers and charge-sensitive amplifiers. The developed double gate junction field-effect transistor can be used in signal readout devices required in the analog interfaces of space instrument sensors and nuclear electronics.